Resonance Scattering and Absorption of an Extraordinary Plane Wave by a Cylindrical Irregularity in a Magnetoplasma - Ivoninsky, A. V.; Kudrin, A. V.; Shchapina, N. V. (Radiophysics and quantum electronics, 2024)
We study resonance scattering of an extraordinary plane electromagnetic wave by a cylindrical magnetic-field-aligned decreased-density irregularity located in a background magnetoplasma. The emphasis is placed on the influence of smoothing the boundary of such an irregularity on the characteristics of its surface and volume plasmon resonances in comparison with the case of a stepwise plasma density profile. The frequency dependences of the amplitude coefficients of the electromagnetic field and the effective scattering and absorption cross sections (per unit length of the cylindrical irregularity) are obtained for different values of the width of the nonuniform region and its radius. A qualitative change in the behavior of the scattering and absorption cross sections is demonstrated, which is caused by energy dissipation at the upper hybrid resonance of the weakly collisional plasma inside the cylindrical irregularity with a monotonic profile of the plasma density, as compared to the case of a similar sharp-walled irregularity.